Inflation targeting and the role of money in a model with sticky prices and sticky money - Antti Ripatti (Bank of Finland, 1997)
In order to study the role of money in an inflation targeting regime for monetary policy, we compare the interest rate and money as monetary policy instruments.Our dynamic stochastic general equilibrium model combines the money-in-the-utility-function approach with sticky prices.We allow for time-varying preferences for real money balances, ie velocity shocks, and stochastic aggregate costs in production, ie 'technology shocks'.We show that conditioning the interest rate on the expected future cost change can be used to achieve constant inflation or constant inflation expectations.The assumed adjustment costs in 'money demand' lead to an equilibrium in which inflation can be controlled by money growth without information on the current state of the economy. Finally, we discuss the tradeoff between money and the interest rate as a monetary policy instrument.The result depends on the parameter stability of the cost change process relative to that of the 'money demand' function.
URN:NBN:fi:bof-20140807379
Keywords: E31; E41; E52; 330; monetary transmission mechanism; money-in-the-utility-function model; sticky prices; technology shock; monetary policy strategy